Launch of the second phase of the negotiations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
On October 4th 2003 the first regionally based second phase of the EPA negotiations was begun between the EU and CEMAC - the Central African Economic and Monetary Union - which includes Cameroon, Central African Republic, Chad, Republic of Congo, Gabon, Equatorial Guinea, Sao Tome and Principe. On October 6th the second regionally based second-phase negotiations were launched in west Africa with ECOWAS -the Economic Community of West African States - which includes Cape Verde, Guinea; Gambia, Ghana, Nigeria, Sierra Leone and WAEMA - West African Economic and Monetary Union - which includes. Benin, Burkina Faso, Côte d'Ivoire Guinea Bissau; Mali, Niger, Senegal and Togo......